Beginning teacher resilience in remote Australia: a place-based perspective - Papatraianou, L.; Strangeways, A.; Beltman, Susan; Schuberg Barnes, E. (Routledge, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Enhancing resilience is key to reducing teacher attrition and addressing the challenges of the profession but scant research exists on resilience in regional and remote settings, where there is a shortage of quality, specialist and lead teachers. The aim of this study was to combine ecological and relational perspectives on resilience to examine pre-service and early career teacher resilience in the remote context of central Australia. The findings suggest that beginning teacher resilience in central Australia involves a particular set of enablers and constraints which are characterised by teachers’ capacity to build connections to place, connections as a learner and connections in relationships. A transactional systems model is presented that articulates the dynamism of the resilience processes and offers a way to better understand the ecological interdependencies unique to a particular context and culture. This understanding will enable teachers, initial teacher educators, school leaders and policy makers to better address the challenges facing this profession.